A Review Paper on Influence of Optimized Process Parameter of Friction Stir Welding on Copper and Aluminium Alloy with Various Filler Materials - Saurabh Agrawal; Dr. Abhijeet Ganguly (International Journal of Scientific Research in Civil Engineering, 2025)
Welding stands as a cornerstone process in fabrication and manufacturing. The fusion of materials through the application of heat, Friction Stir Welding operates on a fundamentally different principle. It is the concept of mechanical stirring through "mixing" the materials together while they are in a plasticized state. The specific focus of our research emerges joining Aluminum alloy and copper dissimilar materials through FSW. in the aerospace industry, aluminum alloys are often used for their lightweight properties, while copper's excellent conductivity is essential in electrical systems. The ability to effectively join these materials opens new possibilities for lightweight, high performance components. The primary objective is to achieve the fusion of aluminum alloy and copper without the use of filler materials. This approach allows us to explore the impact of tool geometry on the resulting joint, when applied to dissimilar materials. By introducing filler materials, we seek to enhance the bonding process between the aluminum alloy and copper plates to achieve not only a stronger and more durable joint but also to explore the influence of filler materials on the micro-structural properties of the weld.
Keywords: Friction Stir Welding; dissimilar materials; Aluminum alloy; Tool geometry